The problematization of school mathematics and the design of learning situations in a scenario of teacher education - Cabrera Chim, Luis Manuel; Romano Rivera, Roberto (IE Revista de Investigación Educativa de la REDIECH, 2024)
Designing learning situations requires a theory that guides its rationality and develops professional knowledge. However, many professional development processes leave out the design process and the understanding of the challenges that come with it. The Socioepistemological Theory of Mathematics Education states that the problematization of mathematical knowledge allows the identification of design principles to elaborate learning situations. Thus, it is of interest to understand how teachers articulate the elements of said problematization in the learning situations they develop. For this, the learning situations designed by the teachers were analyzed using three categories: problematization of mathematical knowledge, redesign of school mathematical discourse, and hypothetical learning trajectory. The results show that teachers have difficulties carrying out robust and pertinent problematizations, which favor, among other things, identifying and establishing those practices that regulate the significance of mathematical knowledge. In addition, it reduces the social dimension to establishing contexts in which to work on mathematical content. They also have difficulties incorporating the elements resulting from the problematization in an adequate learning trajectory. Therefore, problematization is necessary but is not enough to design learning situations.